Changes of the palynobiotas in the Mesozoic and Cenozoic of Patagonia: A review - Quattrocchio, Mirta Elena (2011)
This study describes the compositional changes of Mesozoic-Cenozoic palynologic assemblages in Patagonia, the succession of phytogeographic scenarios and some evolutionary key events. The Triassic 'Ipswich Microflora', characterized by bisaccate pollen and high frequencies of trilete spores, represents the warm-temperate province of south-western Gondwana (Dicroidium Flora), followed in time, in Patagonia, near the Triassic/Jurassic boundary, by the 'Classopollis Microflora', indicating warm and (seasonal) arid conditions. Araucariaceans and podocarpaceans grew on Jurassic uplands. The exclusively Early Cretaceous taxa Cyclusphaera and Balmeiopsis (Coniferae) appeared in the Valanginian. The oldest angiospermous pollen types of Argentina appear in the Barremian-Aptian of southern Patagonia. During the Maastrichtian, the Nothofagaceae and Myrtaceae are incoming. In the Palaeocene, a vegetation dominated by tropical elements would have developed in Patagonia. Increasing Nothofagidites frequency in northern Patagonia during the Middle to Late Eocene indicates climatic change from warm to temperate. Of three Early to Middle Miocene phytogeographic provinces (Neotropical-Transitional and Austral), the Transitional one was replaced during the Late Miocene-Pliocene by the xerophytic Proto Espinal/Steppe with a shrubby-herbaceous vegetation. The Pleistocene and Holocene times were characterized by frequent latitudinal and altitudinal changes in the vegetation distribution, as a response to recurrent climatic oscillations, fluctuations of sea level and ice extent, and changing patterns of atmospheric circulation.